QUALITY ASSESSMENT OF ANTIBIOTIC PRESCRIPTIONS IN PAEDIATRIC PRIMARY CARE SETTINGS IN SERBIA, USING EUROPEAN QUALITY INDICATORS. Issue 1 (14th December 2015) - Božić, Bojana; Bajčetić, Milica
Abstract : Objective: The aim of the study was to compare the quality of antibiotic use among children in primary care settings for acute upper respiratory tract infections, acute tonsillitis and acute otitis media (AOM) with the internationally developed disease-specific antibiotic prescribing quality indicators (APQI) and with National Guidelines. Methods: Prescriptions of systemic antibiotics to the paediatric population (<18 years) with three conditions for the period between 2011 and 2013, at the primary level of health care were analysed by using the National Health Insurance Fund's outpatient reimbursement database. Results: During the followed up period acute upper respiratory infections, 42%, acute tonsillitis, 25%, and AOM/myringitis, 2%, represented more than 69% of the all indications for prescribing antibiotics. The percentage of patients prescribed an antibiotic for acute upper respiratory tract infections, acute tonsillitis and acute otitis media (AOM) was above the proposed range (≤20), 87%–96%. The percentage of patients prescribed a recommended antibiotic was below the proposed range (≥80%), 1%–17%, while the adherence rate to National Guidelines was low, 19%–28%. The percentage of patients prescribed quinolones was above the proposed range for AOM (≤5%), 7%. There were no significant differences in indicators value at the regional level in Serbia. Conclusion: Based on results for disease-specific quality indicators for the most common children diseases and low adherence rates with our National guidelines we can conclude that antibiotic use is inappropriate in Serbia.